The British-American coup that ended Australian independence - Pilger, John (The Guardian, 2014)
John Pilger: In 1975 prime minister Gough Whitlam, who has died this week, dared to try to assert his country’s autonomy. The CIA and MI6 made sure he paid the price
Keywords: Australia news; CIA; Gough Whitlam; MI6; UK news; UK security and counter-terrorism; US news; World news; australia coup